Acute Postoperative Pain of Indonesian Patients after Abdominal Surgery - Chanif, Chanif; Petpichetchian, Wongchan; Wimo, Wimo (Department of Nursing, Faculty of Medicine, Diponegoro University, 2012)
Background: Pain is the most common problem found in postoperative patients.Purpose: The study aimed to describe pain intensity and pain distress at the first 24-48 hours experienced by the patients after abdominal surgery.Method: The study employed a descriptive research design. The samples consisted of 40 adult patients older than 18 years who underwent major abdominal surgery under general anesthesia. The patients were admitted at Doctor Kariadi Hospital Semarang, Central Java Province Indonesia during November 2011 to February 2012. A Visual Numeric Rating Scale was used to measure the pain intensity scores and the pain distress scores at the 5th hour after subjects received 30 mg of Ketorolac injection intravenously, a major analgesic drug being used at the studied hospital. Minimum-maximum scores, mean, standard deviation, median and interquartile range were used to describe pain intensity and pain distress.Result: The findings revealed that on average, postoperative patients had experienced moderate to severe pain, both in their report of pain intensity and pain distress as evidenced by the range of scores from 4 to 9 out of 10 and median score of 5 and 6 (IQR = 2), respectively. It indicated that postoperative pain was common symptom found in patients after abdominal surgery.Keywords: pain intensity, pain distress, abdominal surgery.